Differences in parent and youth perceived neighborhood threat on nucleus accumbens-frontoparietal network resting state connectivity and alcohol sipping in children enrolled in the ABCD study - Harris, Julia C.; Liuzzi, Michael T.; Malames, Bo A.; Larson, Christine L.; Lisdahl, Krista M. (Frontiers in Psychiatry, 2023)
Purpose: Evidence has shown neighborhood threat (NT) as a social driver of emotional and brain development. Few studies have examined the relationship between NT and neural function. Altered functional connectivity in the nucleus accumbens (NAcc) with the frontoparietal network (FPN) has been implicated in the development of substance use, however, little is known about perceived NT-related brain function or downstream alcohol sipping during early adolescence. This study examined the longitudinal relationship between youth and combined youth/parent perceived NT, resting state functional connectivity (RSFC) of the NAcc-FPN, and alcohol sipping behavior during late childhood and preadolescence. Methods: This study used data (N=7,744) from baseline to 2-year follow-up (FU) of the Adolescent Brain Cognitive Development Study (ABCD; Release 4.0). Relationships between youth and combined youth/parent perceive NT, alcohol sipping (baseline to two-year FU), and NAcc-FPN (left/right) connectivity, adjusting for demographics, family/peer history of alcohol use, parental monitoring and warmth, externalizing symptoms, and site, were examined in a mediation model via PROCESS in R. Results: Greater youth-reported NT at baseline was significantly associated with lower RSFC between the right (but not left) NAcc-FPN holding covariates constant (R2 = 0.01, B = -0.0019 (unstandardized), F(12, 7,731) = 8.649, p = 0.0087) and increased odds of alcohol sipping at baseline up to the two-year FU (direct effect = 0.0731, 95% CI = 0.0196, 0.1267). RSFC between the right NAcc-FPN did not significantly predict alcohol sipping at the two-year FU (b = -0.0213, SE = 0.42349, p = 0.9599; 95% CI = -0.8086, 0.8512). No significant relationships were observed for combined youth/parent report predicting alcohol sipping or NAcc-FPN connectivity. Conclusions: Findings suggest notable reporting differences in NT. Combined youth/parent report did not reveal significant findings; youth perceived NT was related to increased likelihood of alcohol sipping and lower neural connectivity between the right NAcc-FPN during late childhood and early adolescence. NT context – and source of reporting – may be crucial in examining links with downstream neuronal function and health behaviors. Future research should investigate reward processing and threat as the cohort ages into later adolescence.